PENGGUNAAN FUZZY LOGIC CONTROLLER PADA FILTER AKTIF UNTUK MEREDAM HARMONISA AKIBAT BEBAN NON LINIER DI BALI NATIONAL GOLF RESORT - Kurniawan, Bagus; Arta Wijaya, I Wayan; Rinas, I Wayan (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i03.p10, 2020)
The type of load contained in the electrical system at Bali National Golf Resort is a non linier load. on-linear loads, it can cause harmonics and make a decrease in quality of electric power. Harmonics can be bad impact for the sinusoidal shape of current and voltage waves and then making the electrical system abnormal. To reduce harmonics we need the addition of an active filter. This research will focus on simulating the use of Fuzzy Logic Controller on active filters to reduce harmonics. The simulation is done using MATLAB R2013 software. As the results, The usage of Fuzzy Logic Controller on active filter are able to reduce the harmonics where the current and voltage harmonic values fall, average to 0,86% and 0,11%.